Deficient or R273H and R248W Mutations of p53 Promote Chemoresistance to 5-FU via TCF21/CD44 Axis-Mediated Enhanced Stemness in Colorectal Carcinoma - Gao, Xiaolei; Zheng, Xuan; Zhang, Yixin; Dong, Liying; Sun, Liangjie; Zhao, Na; Ding, Chong; Ma, Zeyun; Wang, Yixiang (Frontiers in Cell and Developmental Biology, 2022)
Background p53 mutations are high-frequent in various human cancers, and reported to contribute to tumor malignance and chemoresistance. In this study, we explored the mechanism by which mutant p53 promotes carcinogenesis and chemoresistance, and provided novel insights into cancer therapy. Materials and methods 409 patients with colorectal carcinoma from TCGA database were subdivided into two groups according to p53 status, namely mutant p53 and wild-type p53, following with GSEA analysis. The differences of clinicopathologic index were also analyzed. Two HCT116 cell lines contain hot spots at codons R273H and R248W of p53 were constructed based on HCT116 with knockout p53, respectively. Cell viability, mobility, clonogenesis and stemness were detected by CCK8, Transwell migration and invasion, colonogenic and sphere formation assays. Resistance to 5-FU was examined by live-dead staining and flow cytometry. qPCR, western blot and luciferase reporter assay were performed to identify that deficient or mutant p53 promoted chemoresistance of colorectal carcinoma cell line HCT116 through TCF21/CD44 signaling pathway, with the following rescue assays by overexpression of TCF21 and knockdown of CD44. Results Patients with recurrence harbor a higher frequency of mutant p53 than those without recurrence (p<0.05). Mutant p53 group developed larger tumor than wild-type one. GSEA analysis showed that oncogenic signatures were enriched in mutant p53 group. Extracellular assays showed that cancer cells with deficient or mutant p53 (R273H and R248W, respectively) promoted colon cancer cells growth, migration, invasion and stemness. The mutant cancer cells also were observed to significantly resistant to 5-FU. Xenografts also confirmed that HCT116 cells harboring deficient or mutant p53 promoted cancer growth and 5-FU tolerance. Luciferase reporter assay showed that deficient or R237H and R248W p53 endowed cancer cells with chemoresistance by activating CD44 via repressing nuclear transcription factor TCF21 expression. Overexpression of TCF21 or knockdown of CD44 could rescue the sensitivity to 5-FU in deficient and mutant p53 HCT116 cell lines. Conclusion Our results, for the first time, reveal a novel deficient or mutant p53/TCF21/CD44 signaling pathway which promotes chemoresistance in colorectal carcinoma. The axis could be an effective therapeutic strategy against deficient or mutant p53-driven chemoresistance.